(untitled) - Walstad, William B. (New York, 2010)
Each chapter contains an introductory statement, a checklist of behavioral objectives, an outline, a list of important terms, fill-in questions, problems and projects, objective questions, and discussion questions. The text’s glossary is repeated in the Study Guide so that the student does not have to go back and forth between books. Many students will find this “portable tutor” indispensable.
Keywords: Economics,Kinh tế học